Association of absolute lymphocyte count and peripheral blood lymphocyte subsets percentage with minimal residual disease at the end of induction in pediatric B cell acute lymphoblastic leukemia. (3rd April 2019) - Pushpam, Deepam; Rajput, Nishi; Chopra, Anita; Vishnubhatla, Sreenivas; Kumari, Mamta; Kumar, Rajive; Bakhshi, Sameer
Abstract: Absolute lymphocyte count (ALC) has been associated with overall survival (OS) and event-free survival, but we do not know if ALC is associated with minimal residual disease (MRD) at the end of induction (EOI) and whether it can be used as surrogate marker in resource limited settings. Immunological differences between MRD-positive and MRD-negative B ALL patients at the EOI are not known at present. This prospective study evaluated the association of ALC and peripheral blood lymphocyte subset percentage at the EOI with MRD. ALC was done at baseline, day 8, and day 15 and at EOI. Assessment for MRD and peripheral blood lymphocyte subset was done at EOI. In 2-year study duration, 197 B cell acute lymphoblastic leukemia (ALL) patients were recruited out of which 150 were analyzed. Peripheral lymphocyte subset percentage was available for 58 patients. We found that ALC at baseline, day 8, day 15, and EOI was not associated with MRD. Day 8 ALC was significantly higher in poor steroid responders (day 8 blasts > 1 × 10 9 cells/l) ( p < 0.0001). At the EOI, CD4 − CD8 + cell percentage in peripheral blood were significantly higher in MRD-positive patients than MRD-negative patients ( p = 0.01). Our study suggests that ALC at any point is not a surrogate marker for MRD. Immunologically MRD-positive and MRD-negative patients differ in CD4 − CD8 + cells. The role of CD8 + T and TCRαβCD3 + T cells in eliminating residual leukemic cells need to be studied further by functional assays.